The Potential Role of Recombinant Hematopoietic Colony-Stimulating Factors in Preventing Infections in the Immunocompromised Host - James Rusthoven (Canadian Journal of Infectious Diseases)
Hematopoietic colony-stimulating factors coordinate the proliferation and maturation of bone marrow and peripheral blood cells during normal hematopoiesis. Most of these factors are now available as recombinant human colony-stimulating factors, and preclinical and clinical testing is proceeding rapidly. Granulocyte and granulocyte/macrophage colony-stimulating factors have been the most extensively studied to date. In human clinical trials, granulocyte colony-stimulating factor improves neutrophil counts and function, reduces episodes of febrile neutropenia, improves neutrophil recovery after disease- or treatment-induced myelosuppression, and reduces the number of serious infections in several neutropenic disease states. Granulocyte/macrophage colony-stimulating factor has similar biological properties but may also improve eosinophil proliferation and function, and platelet cell recovery after myelotoxic bone marrow injury, Interleukin-1 boosts the effects of granulocyte colony-stimulating factor and granulocyte/macrophage colony-stimulating factor, but also may promote the resolution of established infections in conjunction with antibiotics. The therapeutic realities and future therapeutic implications of these agents for the therapy of infections, cancer and hemopoietic disorders are discussed.